Pemanfaatan Eceng Gondok (Eichornia crassipes) dan Ampas Tebu untuk Pembuatan Pakan Ikan Tawes (Barbonymus gonionotus) - Muhammad Fadhil Akbar; Muhammad Azhari; Valencia Aff Neka; Arafsanajani Arif; Choirul Amar Simbolon; Hijral Hamdani; Marini Wijayanti (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Akbar MF, Azhari M, Neka VA, Arif A, Simbolon CA, Hamdani H, Wijayanti M. 2021. Utilization of water hyacinth and sugarcane for making tawes fish feed. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 795-802. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Water hyacinth (Eichornia crassipes) is a weed that is commonly found in lakes and swamps. It is only used as fertilizers and handicrafts in fewer quantities in Indonesia. Biomass of water hyacinth can be a local feed raw material which is expected to be a raw material for fish feed potentially especially herbivorous fish such as tawes fish . In addition to water hyacinth, bagasse waste as raw material for fish feed can be one solution. Technological innovation is needed to increase the nutrient content of sugarcane waste which is still low. Making probiotic fermented feed can be used as an alternative to improve the nutrition and digestibility of feed. Degradation of organic compounds can be done with the help of cellulolytic, ligninolytic, and hemicellulolytic bacteria and fungi. In addition to reducing the quantity of waste, it also supports sustainable aquaculture policies. The study aims to reduce water hyacinth weeds in the waters and to utilize bagasse which was considered waste so far as an alternative feed for herbivorous fish. The results obtained from this review are the manufacture of alternative feeds from water hyacinth and bagasse can be a cheap alternative feed that can support fish growth. It is expected to be an alternative feed made from local weeds and a cheap industrial by-product for herbivorous fish farming.